Data on granulometric composition of calcium phosphate obtained by dispersion method; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Golovanova O. A.; Chikanova E. S.; Malyshev A. V. Andrei Vladimirovich; Mylnikova T. S. Tatyana Stepanovna (2015, 2015)
Title screen